P6 The emergency treatment with levetiracetam or phenytoin in status epilepticus in children: a pragmatic, randomised controlled trial (the 'eclipse' trial). (May 2019) - Appleton, RE; Lyttle, MD; Gamble, C; Bacon, N; Woolfall, K; Messahel, S; Lee, E
Abstract : Aim: Phenytoin is the recommended second-line intravenous anticonvulsant in the management of paediatric convulsive status epilepticus (CSE). Anecdotal data suggest levetiracetam may be as effective as, and safer than phenytoin. The aim of this trial was to compare the effectiveness and safety of both drugs in CSE. Methods: A superiority and open-label, randomised controlled trial (RCT) undertaken in 30 Emergency Departments in the UK. Participants were aged 6 months to <18 years with CSE that required second-line treatment. Randomisation (1:1) was to levetiracetam (40 mg/kg infused over 5 min) or phenytoin (20 mg/kg infused over 20 min) and stratified by centre. Research without prior consent ('deferred consent') was used as CSE is a time-critical emergency. Clinicians followed national treatment algorithms and enrolled participants at the appropriate time point for administration of second-line treatment. The primary outcome was time to CSE-cessation. Analysis was on an intention-to-treat basis. The trial is registered (ISRCTN 22567894 ). Results: Consent was obtained for 286 (152 levetiracetam, 134 phenytoin) randomised and treated participants between July 2015 and April 2018 comprising the primary outcome analysis. Median time (IQR) from randomisation to CSE-cessation was 35 min (20-NA) in the levetiracetam and 45 min (24-NA) in the phenytoin-treated group (adjusted Hazard Ratio 1.17 [95% CI 0.87–1.57; p=0.3). CSE was terminated in 106 (69.6%) of the levetiracetam, and 86 (64.2%) of the phenytoin-treated group. Sensitivity analysis showed no difference between groups using time from start of infusion to CSE-cessation. Five serious adverse events occurred in four participants, one of which was considered related to the drug (severe hypotension in a phenytoin-treated participant). No serious, new or unexpected reactions were observed with levetiracetam. Conclusion: No statistically significant difference was detected between treatments but results, robust across sensitivity analyses, favoured levetiracetam. Serious adverse events were low for both treatments although there are known concerns with the safety profile of phenytoin. This trial suggests levetiracetam be considered as an alternative to phenytoin as the first-choice, second-line treatment of CSE in children.